Assessing Public Works Procurement in the Czech Republic`s over-limit Regime: Survey Results and Recommendations for Contracting Authorities - Matějková, Jitka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article elucidates the findings of a research study on public works procurement within the over-limit regime in the Czech Republic. A comprehensive survey, conducted in May 2023, provides a panoramic view of the current procurement landscape, encompassing aspects such as procurement methods, financing sources, cost considerations, and time allocation.
Keywords: public procurement; evaluation; public bid; public works procurement; contracting authority; Best Value Approach